2019
DOI: 10.1108/bij-01-2019-0039
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of efficiency and productivity in the Indian non-life insurance market

Abstract: Purpose The purpose of this paper is to analyse the performance of the Indian non-life (general) insurance sector in terms of efficiency, productivity and returns-to-scale economies. In addition to this, it identifies the determinants of efficiency. Design/methodology/approach This study employs a two-stage data envelopment analysis (DEA) bootstrap approach to estimate the level and determinants of efficiency. In the first stage, the DEA bootstrap approach is employed to estimate bias-corrected efficiency sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 88 publications
(160 reference statements)
1
37
1
Order By: Relevance
“…The company's age does not impact the company's productivity. Whether it is old or new, it is immaterial for efficiency; this contradicts the findings of Ilyas and Rajasekaran (2019) on "age of the company" significantly positive with technical efficiency.…”
Section: Tobit Regressionmentioning
confidence: 68%
See 2 more Smart Citations
“…The company's age does not impact the company's productivity. Whether it is old or new, it is immaterial for efficiency; this contradicts the findings of Ilyas and Rajasekaran (2019) on "age of the company" significantly positive with technical efficiency.…”
Section: Tobit Regressionmentioning
confidence: 68%
“…However, in the study done by M. M. Jaloudi (2019), it was concluded that reinsurance is insignificant to insurers' efficiency. We expect a negative relationship for reinsurance like Cummins et al (2010) and (Ilyas & Rajasekaran, 2019)…”
Section: Reinsurance Activitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies reviewed in the said paper applied DEA to calculate the efficiency of firms from various backgrounds, with multiple inputs and outputs. There are other studies in literature (Borges et al, 2008;Cummins & Weiss, 2013;Ilyas Ashiq, 2019;Mandal, 2014), which calculated the efficiency of insurance companies by adopting DEA as tool for efficiency measurement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of the two main kinds of insurance, Life insurance, where the insurer invests the insured’s savings undertaking to pay a capital or an income in case of a life event, such as death; and P&C—Property and Casualty insurance, that protects the insured against possible losses deriving from damages to persons or objects (Marchionni, 2006 ), we concentrate on insurance companies solely in the P&C insurance business. The P&C segment is particularly detrimental for the market as it deals with almost any kind of risk (Ilyas & Rajasekaran, 2019 ) affecting daily and business continuity. Indeed, process digitalization (such as for sales and distribution) and achievement of higher efficiency are among the top trends in the P&C market according to practitioners (EY, 2019 ), with the promise of promoting efficiency in processes that are particularly relevant for this kind of insurance (e.g.…”
Section: Introductionmentioning
confidence: 99%